Fresno March and Rally Against War in El Salvador - Watkins, Howard::::::::: (1981)
Marchers at Belmont underpass at H Street; Posters "Don't Register for EXXON'S War!", "Stop the Draft," "Stop the Draft Refuse to Register," "Reagan is a Scab"